Many-to-one function of cat-like mandibles highlights a continuum of sabre-tooth adaptations. Issue 1988 (7th December 2022) - Chatar, Narimane; Fischer, Valentin; Tseng, Z. Jack
Abstract : Cat-like carnivorans are a textbook example of convergent evolution, with distinct morphological differences between taxa with short or elongated upper canines, the latter often being interpreted as an adaptation to bite at large angles and subdue large prey. This interpretation of the sabre-tooth condition is reinforced by a reduced taxonomic sampling in some studies, often focusing on highly derived taxa or using simplified morphological models. Moreover, most biomechanical analyses focus on biting scenarios at small gapes, ideal for modern carnivora but ill-suited to test for subduction of large prey by sabre-toothed taxa. In this contribution, we present the largest three-dimensional collection-based muscle-induced biting simulations on cat-like carnivorans by running a total of 1074 analyses on 17 different taxa at three different biting angles (30°, 60° and 90°) including both morphologies. While our results show a clear adaptation of extreme sabre-toothed taxa to bite at larger angles in terms of stress distribution, other performance variables display surprising similarities between all forms at the different angles tested, highlighting a continuous rather than bipolar spectrum of hunting methods in cat-like carnivorans and demonstrating a wide functional disparity and nuances of the sabre-tooth condition that cannot simply be characterized by specialized feeding biomechanics.